Fenomena PHK Masa Pandemi Covid-19 dan Dampaknya Terhadap Fresh Graduate Jurusan Ilmu EKonomi Universitas Negeri Surabaya - Akhmad, Rizqiya Fauziyah; Rachmawati, Lucky (Independent: Journal of Economics, 2021)
This research was conducted to discuss the impact that occurred due to the termination of employment (PHK) by companies due to the COVID-19 pandemi on jobseekers, especially fresh graduates at the Department of Economics, Universitas Negeri Surabaya.. The COVID-19 pandemi has had a significant impact on several aspects such as economic and employment aspects, with the layoff policy in this pandemi era, as well as the unstable state of the economy, causing unemployment to increase. The method used in this research is descriptive qualitative method with a phenomological approach. The results of the study are based on the results of interviews that have been conducted with the informants and are also compared with previous theories and studies. Freshgraduate majoring in Economics, State Universitas Negeri Surabaya as a jobseeker felt the impact of the company’s policy of layoffs during the COVID-19 pandemi. Hard skills and soft skills are the main foundation for competing in the world of work and the creation of superior human resources in the midst of today’s global changes. Keywords: COVID-19, freshgraduate, PHK, unemployment